PilotHub - Fadzly Izzat, Aisy Firas Eamina; Mohd Ridzuan, Insyirah Hayati; Mohd Roslan, Noor Maisarah; Noor Hijat, Noor Nayli; Mohd Ridzuan, Safwah Hayati; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Efficient pilotage is crucial for safe, timely, and cost-effective port operations, but traditional systems often struggle with delays, high costs, and poor coordination. As part of our IBM554 International Trade course at Universiti Teknologi MARA, we developed PilotHub—an innovative mobile app designed to modernize pilotage operations. Pilots face challenges like delayed ship movements, disrupted schedules, and excessive paperwork. PilotHub solves these problems using AI for smart pilot assignment, AR for safer navigation, and digital tools to replace paperwork. The app is mobile-friendly, letting pilots and dispatchers coordinate in real-time. Pilots can log in to see their dashboard with job details, weather, and tide info. They receive assignments based on license type and ship requirements, reducing wait times. AR helps guide ships safely in port, and digital logs make reporting fast and easy. PilotHub is designed for port authorities, pilot services, and shipping companies, offering easy integration and global scalability. We also surveyed 30 maritime professionals to gather feedback and improve the app. Overall, PilotHub improves safety, reduces delays, and streamlines operations, setting a new standard for smart port management.